Expression Patterns of Three Important Hormone Genes and Respiratory Metabolism in Antheraea pernyi during Pupal Diapause under a Long Photoperiod - Qi Wang; Yu-Tong Luo; Yong Wang; De-Yi Wang; Xiao-Xia Duan; Yao-Ting Zhang; Yu-Meng Bian; Wei Liu; Li Qin (Insects, 2021)
The Chinese oak silkworm is commonly used in pupal diapause research. In this study, a long photoperiod was used to trigger pupal diapause termination. Genes encoding three hormones, namely prothoracicotropic hormone (PTTH), ecdysis triggering hormone (ETH), and eclosion hormone (EH), were studied. Additionally, ecdysteroids (mainly 20-hydroxyecdysone, 20E) were quantified by HPLC. Pupal diapause stage was determined by measuring respiratory intensity. The pupae enter a low metabolic rate, which starts approximately 1 month after pupal emergence. ApPTTH expression showed a small increase at 14 days and then a larger increase from 35 days under the long photoperiod treatment. A similar pattern was observed for the titer of 20E in the hemolymph. However, ApETH expression later increased under the long photoperiod treatment (42 days) just before eclosion. Moreover, ApEH expression increased from 21 to 35 days, and then decreased before ecdysis. These results suggest that hormone-related gene expression is closely related to pupal development. Our study lays a foundation for future diapause studies in A. pernyi.